Unusual dimeric flavonoids (brachydins) induce ultrastructural membrane alterations associated with antitumor activity in cancer cell lines - Maciel-Silva, Vera Lucia; Rocha, Claudia Quintino da; Alencar, Luciana Magalhães Rebelo; Castelo-Branco, Patrícia Valéria; Sousa, Israel Higino de; Azevedo-Santos, Ana Paula; Vale, André Alvares Marques; Monteiro, Silvio Gomes; Soares, Rossy-Eric Pereira; Guimarães, Sulayne Janayna Araujo; Nascimento, Jessyane Rodrigues do [UNESP]; Pereira, Silma Regina Ferreira (Taylor & Francis, 2022)
Notwithstanding the advances in molecular target-based drugs, chemotherapy remains the most common cancer treatment, despite its high toxicity. Consequently, effective anticancer therapies with fewer adverse effects are needed. Therefore, this study aimed to determine the anticancer activity of the dichloromethane fraction (DCMF) isolated from Arrabidae brachypoda roots, whose components are three unusual dimeric flavonoids. The toxicity of DCMF was investigated in breast (MCF-7), prostate (DU145), and cervical (HeLa) tumor cells, as well as non-tumor cells (PNT2), using sulforhodamine B (cell viability), Comet (genotoxicity), clonogenicity (reproductive capacity) and wound healing (cell migration) assays, and atomic force microscopy (AFM) for ultrastructural cell membrane alterations. Molecular docking revealed affinity between albumin and each rare flavonoid, supporting the impact of fetal bovine serum in DCMF antitumor activity. The IC50 values for MCF7, HeLa, and DU145 were 2.77, 2.46, and 2.51 µg/mL, respectively, and 4.08 µg/mL for PNT2. DCFM was not genotoxic to tumor or normal cells when exposed to twice the IC50 for up to 24 h, but it inhibited tumor cell migration and reproduction compared to normal cells. Additionally, AFM revealed alterations in the ultrastructure of tumor nuclear membrane surfaces, with a positive correlation between DCMF concentration and tumor cell roughness. Finally, we found a negative correlation between roughness and the ability of DCMF-treated tumor cells to migrate and form colonies with more than 50 cells. These findings suggest that DCFM acts by causing ultrastructural changes in tumor cell membranes while having fewer toxicological effects on normal cells.
Keywords: Arrabidaea brachypoda; atomic force microscope; cell membrane; chemotherapy; natural products